The causes of risk in fuel supply chains and their role in energy security. (15th November 2021) - Axon, C.J.; Darton, R.C.
Abstract: Managing risk is of central importance in achieving energy security, yet a methodology for identifying and assessing all relevant risks has previously been lacking. From an extensive review of risk and the operation of fuel supply chains, 34 distinct generic causes of risk have been recognised. These risks were analysed for the UK's energy system, considered as 19 fuel supply chains (each with six stages), and scored by likelihood and impact on the supply chain (accounting for resilience). A risk matrix was constructed recording the risks encountered at each stage for each fuel. For the UK, the three causes with the greatest total score were 'lack of access to capital', 'changing policy or regulatory framework' and 'significant public concern', all of which were amongst the eight causes of risk noted as most significant at an expert verification workshop. This methodology yields a credible and direct quantification of risk for a national energy system – an indicator of energy security. It does not require the assignment of weighting factors to various contributory characteristics, often arbitrarily chosen in other approaches. It is suggested that the seven most prevalent causes of risk, that occur for nearly all fuels and all stages, may be systemic in nature. The method offers sufficient flexibility to make it readily applicable to other nations, regions, or sites, and other types of supply chain. Highlights: We propose a transparent risk assessment method for energy security analyses. Our method identifies drivers of systemic risk in fuel supply chains. We conceptualise risks as having micro-, meso-, or macro-scale effects. Main risks: access to capital, changing policy/regulation, and public concern. Our method is robust to uncertainty in individual risk scores.